Perspektif Etis tentang Transplantasi Organ Tubuh: Telaah Kritis atas Pandangan Syekh Yusri Rusydi Sayyid Jabr al-Hasani - Siti Khamidatus Sholikhah; Zezen Zainul Ali (Indonesian Journal of Humanities and Social Sciences, 2023)
Organ transplantation is a medical procedure involving the transfer of organs, cells, or tissues from a donor to a recipient to address organ failure, damage, or dysfunction. This study delves into the legal and ethical aspects of organ transplantation, focusing on the perspective of Sheikh Yusri Rusydi Sayyid Jabr al-Hasani. Employing a qualitative literature review approach, primary sources such as books, journals, websites, and relevant materials were analyzed. The research reveals that Sheikh Yusri Rusydi Sayyid Jabr al-Hasani considers organ transplantation to be prohibited (haram) because it involves the removal and transplantation of organs entrusted to individuals by Allah SWT as a testament to human uniqueness. This act is seen as a departure from the natural order (fitrah) set by Allah SWT, potentially causing immune complications akin to the condition of AIDS patients. It is important to note that organ transplantation is not merely a means to extend life or evade mortality but rather a transformation of one's way of life, transitioning from a blood-dependent existence to a non-blood-dependent one. This study acknowledges limitations in terms of analysis and the applicability of its findings, primarily stemming from its reliance on a singular scholarly perspective. Therefore, it underscores the need for more comprehensive research, particularly in the context of organ donation and wills, to further enrich our understanding of this complex issue.